2021
DOI: 10.1093/pm/pnab225
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Specific Alterations in Brain Function in Patients with Primary Dysmenorrhea

Abstract: Objective Recent neuroimaging studies have found that brain function is abnormal in primary dysmenorrhea (PDM). The present study aimed to explore frequency-specific brain alterations and their occurrence in the PDM. Methods Forty-seven patients with PDM and 36 matched healthy controls were enrolled in the study and underwent resting-state functional magnetic resonance imaging. The alterations in brain function in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
0
13
1
Order By: Relevance
“…patients with PDM exhibited frequency-dependent distribution patterns of brain activity. Specifically, these altered brain areas, especially in the central executive network (CEN), default mode network (DMN), sensorimotor network (SMN), and the hippocampus (Yu et al, 2021). Notably, we observed a decreased gFCD in DLPFC at the Slow-5 band and an increased gFCD in the hippocampus at the Slow-3 band, indicating that the patients with PDM showed aberrant pain processing.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…patients with PDM exhibited frequency-dependent distribution patterns of brain activity. Specifically, these altered brain areas, especially in the central executive network (CEN), default mode network (DMN), sensorimotor network (SMN), and the hippocampus (Yu et al, 2021). Notably, we observed a decreased gFCD in DLPFC at the Slow-5 band and an increased gFCD in the hippocampus at the Slow-3 band, indicating that the patients with PDM showed aberrant pain processing.…”
Section: Introductionmentioning
confidence: 68%
“…The inclusion and exclusion criteria in this study were similar to our previous study (Yu et al, 2021). The patients with PDM were recruited primarily through the gynecology outpatient and inpatient sections at the Affiliated Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu University of Traditional Chinese Medicine, Sichuan University, Southwest University of Finance and Economics, Southwest Jiaotong University, and Southwest University for Nationalities.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a genuine type of chronic pain, recent neuroimaging studies have indicated that the brain structural and functional alteration is also involved in the pathophysiological of PDM (Low et al, 2018). The brain functional alteration in PDM patients has been found in descending pain modulatory systems and default mode network (Wei et al, 2016;Wu et al, 2016;Yu et al, 2021). For the structural brain, the abnormalities have been found in the regional gray matter volume (Tu et al, 2010(Tu et al, , 2013 and cortical thickness (Liu et al, 2016), mainly involved in pain perception, transmission, modulation, as well as emotion processing (Low et al, 2018;Tu et al, 2013;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%